(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: E-cigarettes have quickly become a popular alternative to traditional cigarettes, often promoted as a less harmful method of nicotine consumption. Their rising use, especially among young adults has sparked concerns while also fueling an ongoing public health debate. This study aims to determine the prevalence of e-cigarette smoking, assess knowledge and attitudes and identify associated factors. Method: A cross-sectional survey in Lahore examined e-cigarette use among university students aged 18– 24, recruited via purposive sampling. Data was collected using a self-administered questionnaire, with quantitative data analyzed using descriptive and inferential statistics, and qualitative responses analyzed thematically. Ethical approval was obtained, ensuring participant confidentiality and anonymity. Results: According to study findings, 41.6% (n=132) of university students (n=320) had tried e- cigarettes, driven by curiosity, social influences, and quitting smoking. Among those who ever used e-cigarettes, a significant portion (around 68%) reported using them for at least two years. Nearly half (around 34%) indicated using them for more than four years. Conclusion: The survey highlights the widespread use of e-cigarettes among university students, driven by curiosity, social influences, and smoking cessation motives. It underscores the need for more research on the long-term health effects and the role of e-cigarettes in smoking cessation, while emphasizing public support for age restrictions and flavor regulations.